2017
DOI: 10.3892/mmr.2017.8265
|View full text |Cite
|
Sign up to set email alerts
|

Association of aquaporin‑1 with tumor migration, invasion and vasculogenic mimicry in glioblastoma multiforme

Abstract: The present study aimed to assess the expression and functional role of aquaporin-1 (AQP1) in glioblastoma multiforme (GBM) migration, invasion and vasculogenic mimicry (VM). In the primary human gliomas and human glioma‑derived cell lines tested, it was observed that the expression of AQP1 was upregulated. In addition, it was demonstrated that silencing of AQP1 expression resulted in decreased migration and invasion, in addition to vasculogenic mimicry in vitro. It was additionally observed that silencing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
2
12
0
1
Order By: Relevance
“…In lung cancer cells, AQP1 knockdown had inhibitory effects on cancer cell proliferation and migration along with the downregulation of MMP‐9 expression 28 . It was also demonstrated that silencing of AQP1 expression resulted in decreased MMP‐9 expression in GBM cells 29 . In this study, forced expression of AQP1 also significantly upregulated MMP‐9 activities (Figure 3M).…”
Section: Discussionsupporting
confidence: 60%
“…In lung cancer cells, AQP1 knockdown had inhibitory effects on cancer cell proliferation and migration along with the downregulation of MMP‐9 expression 28 . It was also demonstrated that silencing of AQP1 expression resulted in decreased MMP‐9 expression in GBM cells 29 . In this study, forced expression of AQP1 also significantly upregulated MMP‐9 activities (Figure 3M).…”
Section: Discussionsupporting
confidence: 60%
“…83 Aquaporin-1 may play a role in VM in glioblastoma, and it can be used as a new diagnostic biomarker and a potential therapeutic target. 84 In oligodendroglioma, downregulation of galectin-1 gene expression, a significant decrease in brain expressed X-linked 2 expression, and inhibition of VM may present new therapeutic strategies for reducing chemotherapy resistance. 85 A histone deacetylase inhibitor has also been identified as a promising candidate for VM inhibition in glioblastoma.…”
Section: Cytokine Familymentioning
confidence: 99%
“…Recent studies, have highlighted the important role of ion channels in GBM cell proliferation and aggressiveness (Sforna et al, 2017; Wong et al, 2018; Yang et al, 2017, 2018; D’Alessandro et al, 2018). In particular, it has been shown that the swelling-activated Cl − current is over-expressed in GBM cell lines (Catacuzzeno et al, 2014; Sforna et al, 2017), and contributes substantially to cell proliferation through activation of JAK2/STAT3 and PI3K/AKT signaling pathways (Wong et al, 2018).…”
Section: Gbm-induced Abnormal Cell-proliferationmentioning
confidence: 99%